POLR2A Promotes the Proliferation of Gastric Cancer Cells by Advancing the Overall Cell Cycle Progression - Jiang, Qiuyu; Zhang, Jinyuan; Li, Fang; Ma, Xiaoping; Wu, Fei; Miao, Jiyu; Li, Qian; Wang, Xiaofei; Sun, Ruifang; Yang, Yang; Zhao, Lingyu; Huang, Chen (Frontiers in Genetics, 2021)
RNA polymerase II subunit A (POLR2A) is the largest subunit encoding RNA polymerase II and closely related to cancer progression. However, the biological role and underlying molecular mechanism of POLR2A in gastric cancer (GC) are still unclear. Our study demonstrated that POLR2A was highly expressed in GC tissue and promoted the proliferation of GC in vitro and in vivo. We also found that POLR2A participated in the transcriptional regulation of cyclins and cyclin-dependent kinases (CDKs) at each stage and promoted their expression, indicated POLR2A’s overall promotion of cell cycle progression. Moreover, POLR2A inhibited GC cell apoptosis and promoted GC cell migration. Our results indicate that POLR2A play an oncogene role in GC, which may be an important factor involved in the occurrence and development of GC.